EFFECT OF ADDITION OF GROWTH REGULATOR SUBSTANCE CONCENTRATION ON THE GROWTH Tetraselmis chuii CULTURE IN LABORATORY SCALE - Diki Restu Setiawan; Ganjar Adhywirawan Sutarjo; Riza Rahman Hakim (Universitas Muhammadiyah Malang, 2023)
Tetraselmis chuii is one type of phytoplankton that can be used as a natural food source. According to FAO-UN (2016) Tetraselmis chuii has 83,400% protein content, 32,500% carbohydrate and 45,700% lipid. Higher than Chaetoceros gracili, Nannochloropsis oculata, Dunaliellatertiolecta and Isochrysis galbana. In cultured phytoplankton nutrient composition of the culture medium was very instrumental in the growth. Microalgae growth with culture can reach optimum by mixing sea water with nutrients that are not contained in the sea water. Related to this, various efforts have been made in an effort to increase the growth of natural feed, both cultivation methods and the addition of various growth substances. One substance that has the potential to increase the growth of natural feed is the use of growth hormones to increase the growth of natural feed, namely through population density, he application form is by adding growth regulators. This research was carried out at the Natural Feed Laboratory at the Center for Aquaculture of Sea Water Fisheries, Situbondo. This study used Completely Randomized Design (CRD) yanang cultured laboratory scale with 7 treatments and 4 repetitions. The treatment in this study was the administration of 2.4-D-Acid Growth Regulating Substances with different doses. The main parameters used include growth measurements by calculating the density and growth rates Tetraselmis chuii. Furthermore, the data were analyzed using ANOVA followed by LSD test. The addition concentration of plant growth regulator effect on cell density and growth rate Tetraselmis chuii culture laboratory scale. Provision of plant growth regulator with konssentrasi 5 ml + 1 ml Walne produce the highest density of 2.323125 cells/ml and a maximum growth rate that is 173 269 cells/ml/day.